Urgensi Integrasi Pengaturan Mekanisme Keadilan Restoratif dalam Sistem Peradilan Pidana di Indonesia - Rahma, Nabila Aulia; Toloh, Pascal (Jurnal Hukum & Pembangunan, 2022)
Conventional criminal law has always been synonymous with prison, where the settlement can result in the exclusion of the right to a sense of justice for victims because of their disproportionate position. This situation encourages the emergence of the concept of restorative justice, where based on this concept, criminal cases are resolved by involving perpetrators, communities and victims. However, at the regulatory level, the concept of restorative justice is set differently in various rules, which have not been synchronized, such as the internal rules of the Indonesian Police, the Attorney General's Office and the Supreme Court. Inconsistencies in these norms can have an impact on the level of implementation that is not in line with the formulation of an integrated criminal justice system or "Integrated Criminal Justice System". This study aims to determine the problems of restorative justice arrangements in the national legal system in Indonesia and how urgent the integration of restorative justice arrangements in the national legal system in Indonesia is. The research method used in this study is a normative-juridical legal study with a statue approach, conceptual approach, and also comparative approach. The results show: That there are still differences in interpretation and inconsistencies between regulations on restorative justice in the criminal justice system in Indonesia, so a formulation of regulations on restorative justice in the criminal justice system is needed so that the implementation of restorative justice mechanisms can be implemented optimally. The author will focus on the integration of regulations regarding restorative justice mechanisms in the Code of Criminal Procedure (KUHAP) so that it can be in line with the conception of an integrated criminal justice system. In addition, to organize quality regulations, the author will analyze with a comparative approach restorative justice arrangements in other countries.